Increased WIP1 Expression With Aging Suppresses the Capacity of Oocytes to Respond to and Repair DNA Damage - Leem, Jiyeon; Bai, Guang-Yu; Kim, Jae-Sung; Oh, Jeong Su (Frontiers in Cell and Developmental Biology, 2021)
If fertilization does not occur for a prolonged time after ovulation, oocytes undergo a time-dependent deterioration in quality in vivo and in vitro, referred to as postovulatory aging. The DNA damage response is thought to decline with aging, but little is known about how mammalian oocytes respond to the DNA damage during in vitro postovulatory aging. Here we show that increased WIP1 during in vitro postovulatory aging suppresses the capacity of oocytes to respond to and repair DNA damage. During in vitro aging, oocytes progressively lost their capacity to respond to DNA double-strand breaks, which corresponded with an increase in WIP1 expression. Increased WIP1 impaired the amplification of γ-H2AX signaling, which reduced the DNA repair capacity. WIP1 inhibition restored the DNA repair capacity, which prevented deterioration in oocyte quality and improved the fertilization and developmental competence of aged oocytes. Importantly, WIP1 was also found to be high in maternally aged oocytes, and WIP1 inhibition enhanced the DNA repair capacity of maternally aged oocytes. Therefore, our results demonstrate that increased WIP1 is responsible for the age-related decline in DNA repair capacity in oocytes, and WIP1 inhibition could restore DNA repair capacity in aged oocytes.